Podatność na rozkład biologiczny i potencjał biogazowy mieszanin odpadów = Biodegradability and methane potential of waste - Suchowska-Kisielewicz, Monika; Sadecka, Zofia; Sieciechowicz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The development and implementation of clean energy technologies is now an important task. The process of fermentation of organic waste is an especially attractive source of renewable energy generation is. Practically any organic material which does not contain inhibitors may be substrate used for the biogas production. The article presents the results on organic waste mixtures ability to be biodegradable. This ability was tested by both aerobic (AT4) and anaerobic (BMP) tests.
Keywords: odpady organiczne; AT4; BMP; organic wastes; AT4 test; BMP test